PHYSICS EDUCATION TECHNOLOGY: AS A STRATEGY IN THE DEVELOPMENT OF AN INSTRUCTIONAL MATERIAL IN TEACHING CHEMISTRY - De Jesus Bactan, Charmaine (LP2M Universitas Bina Mandiri Gorontalo, 2023)
The purpose of the study is to develop a PhET-inspired instructional material that supports the use of investigative practical work in secondary school Chemistry. This study employed a Design-Based Research (DBR) design. In the preliminary data, the researcher surveyed 7 experienced public junior high school chemistry teachers. Analysis of the current practices in teaching Chemistry shows that most of the Grade-10 Science teachers in the selected schools are female and were trained in Chemistry teaching.The first prototype of materials designed was appraised by 2 college instructors, one master teacher in science, and a professional teacher with a specialization in Chemistry teaching. The feedback from the experts was used to redesign and refine the materials producing the second-level prototype which was tried out by two experienced teachers with their selected students. Teacher interviews in the implementation of the instructional materials found that (i) the instructional material complies with the content standards of the DepEd Curriculum Guide for the selected topics, (ii) the selected topics in Chemistry specifically in the areas of Additional Activity, Motivation, and Investigative Practical Work, (iii) it guides the teacher to be a facilitator of the lesson and not the sole producer of information, (iv) it guides the student to produce efficient scientific explanation by guiding them to provide claim, evidence, and reasoning, (v) the PhET simulation serve as readily available alternative for laboratory equipment. The issues found from lesson observations and teacher interviews were used to redesign the materials thus developing the final model of exemplary materials.